Management of inherited thrombophilia in pregnancy. (July 2016) - Ormesher, Laura; Simcox, Louise; Tower, Clare; Greer, Ian A
Adverse pregnancy outcomes, such as pregnancy loss and pre-eclampsia, are associated with thrombotic mechanisms and thrombophilia. Antithrombotic interventions, particularly low-molecular-weight heparin, have been investigated in women identified by previous pregnancy outcome; however, the results have been inconsistent. This may reflect heterogeneity of both the study groups and the disease processes resulting in inadequate stratification to guide antithrombotic interventions. Furthermore, the variation in gestation at initiation of low-molecular-weight heparin treatment might be important. Despite limited evidence of efficacy, low-molecular-weight heparin is often used in an attempt to prevent these complications, owing to the lack of other effective treatments and its perceived safety in pregnancy. Research is required to better understand the disease processes, identify possible biomarkers and thereby more homogeneous groups for targeted treatment.